Institutional Risk Preference and Asymmetric Role of Institutional Distance: An Examination on the OFDI of China - Yawei Qi; Guangping Rao (Discrete Dynamics in Nature and Society)
With the implementation of the “Going Out” policy and the “Belt and Road” initiative, Chinese outward foreign direct investment (OFDI) in the countries along the “Belt and Road” increased substantially in the past decade. This paper analyzes the impact of institutional distance on Chinese OFDI and whether Chinese OFDI exhibits institutional risk preferences, using data on Chinese OFDI in 41 countries along the “Belt and Road” for the period from 2003 to 2018. We find that political institutional distance and economic institutional distance are both positively related to China’s OFDI scale, while cultural distance has a negative impact on the investment scale. We also find that institutional distance has an asymmetric effect on China’s OFDI. In particular, the worse the host country’s political environment, the larger the Chinese OFDI, indicating that Chinese OFDI exhibits the political institutional risk preference. On the other hand, Chinese multinational enterprises are more willing to invest in host countries with high economic freedom. Culture institution environment of the host country has a positive but insignificant impact on the Chinese OFDI scale, indicating that Chinese OFDI shows the characteristics of cultural distance proximity.